Fighting corruption with cultural dynamics: when legal-origins, religious-influences and existing corruption-control levels matter - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
Are there different determinants in the fight against corruption across developing countries? Why are some countries more effective at battling corruption than others? To investigate these concerns we examine the determinants of corruption-control throughout the conditional distribution of the fight against corruption using panel data from 46 African countries for the period 2002-2010. Our findings demonstrate that blanket corruption-control policies are unlikely to succeed equally across countries with different legal-traditions, religious-influences and political wills in the fight against corruption. Thus to be effective, corruption policies should be contingent on the prevailing levels of corruption-control and tailored differently across the best and worst corruption-fighting countries especially with respect to democracy, population growth and economic prosperity.
Keywords: C10; H10; K10; O10; O55; 330; Corruption; Democracy; Government quality; Quantile regression; Africa